Lecturers’ Strategies to Enhance PGMI Students’ Pedagogical Competence Through Digital Learning at Nurul Jadid University - Feriska Listrianti; Rofita Aprilia Putri; Syahadatinah Firdaus; Nimas Naila Maratus; Alfi Khoirin Nisak; Nur Iklimah Zuhri (Global Education Journal, 2025)
This study aims to analyze the implementation of technology-based learning strategies in enhancing the pedagogical competence of PGMI students at Nurul Jadid University. A descriptive qualitative approach was employed, involving respondents consisting of course instructors and 25 final-semester students. Data were collected through classroom observations, structured interviews, document reviews, and field notes. Thematic analysis was conducted to identify patterns in technology use and its impact on students’ pedagogical skills. The findings indicate that the application of blended learning provides high flexibility while maintaining the quality of academic interaction between lecturers and students. The use of interactive media, such as instructional videos, infographics, and digital quizzes, was found to improve content comprehension, stimulate active participation, and reduce learning fatigue. Furthermore, technology-based projects contributed to strengthening practical skills, creativity, teamwork, and students’ adaptability to advancements in educational technology. These results affirm that technology-based strategies are effective in preparing PGMI teacher candidates to meet the demands of modern education, while simultaneously enhancing their independent learning, self-confidence, and collaborative skills.